Effects of personality and the problem of stress and risky eating behaviors in the non-obese university population - Zapata Piña, Karina Mariela (2020)
The aim of this article is to establish the first findings, at Metropolitan Lima level, about the problem of stress and risky eating behaviors and personality in the non-obese university population. One of the most critical stages to reinforce these new habits is during childhood; however, due to the changes that are taking place at contextual and technological level, the university stage is also considered as a critical stage for the human being. Issues such as stress are somehow soothed by certain personality features and by habits acquired during childhood. However, it is important to be able to set up a study to identify more factors that intervene in this problem and, in turn, find prevention methods in order to foster healthy eating behaviors in the students.